David Coleman conducts "Grandi momenti di danza" -- With the Etoiles, Soloists, and Corps de Ballet of La Scala Teatro Alla Scala - Bournonville, August; Legris, Manuel; Kratz, Philippe; Dell'Ara, Ugo; Bigonzetti, Mauro; Nureyev, Rudolf; Nureyev, Rudolf (RAI, 2020)
Milan's beloved Teatro alla Scala welcomes you for an evening filled to the brim with the biggest names on the world ballet stage! Let yourself be dazzled throughout this evening that begins with excerpts from La Sylphide, in the classic choreography by the great August Bournonville. Masterworks aplenty appear on the program of this gala event, with timeless ballet classics like Le Spectre de la Rose by Nureyev after Fokine, and gorgeous contemporary works like Le Corsaire by Manuel Legris ... Photo © Brescia/Amisano - Teatro alla Scala
Keywords: ballet; Internet videos